Approximation on the Quadratic Reciprocal Functional Equation. (20th February 2014) - Bodaghi, Abasalt; Kim, Sang Og
Abstract : The quadratic reciprocal functional equation is introduced. The Ulam stability problem for anϵ -quadratic reciprocal mappingf : X → Y between nonzero real numbers is solved. The Găvruţa stability for the quadratic reciprocal functional equations is established as well.